Quality of Front-Line Work = Human Resource Management? - Bencsik, Andrea; Feher, Judit (Communications - Scientific letters of the University of Zilina, 2006)
“Good quality” human resource management is a source of competitive advantage for companies in the field of personal services, especially in customer service. Customers’ opinion of overall service quality is very much influenced by the impression, when they encounter front-line staff. HR management can be regarded as “good quality” if it is able to ensure that staff members working on the front line are professionally and emotionally well-prepared, and committed. It can only perform its function if it is able to adopt a new approach. As an internal service provider it strives to support workers in both meeting corporate requirements and achieving their individual goals. In the case of service companies with networks change inevitably requires giving local management a broader scope of authority in the field of human resource management, as well as preparing local management for carrying out its increasing range of functions.